Things That Growl In The Night - Jim Mason (Symphony in the Flint Hills, 2010)
You cannot say this about a lot of the Great Plains, but the Flint Hills of today bear a strong resemblance to what they looked like before European colonization, and that is one of their many charms.
Keywords: North America; bison; pronghorn; elk; deer; grazers; ecosystem; prairie; grassland; grass; nature; predator; food; cougar; wolves; grizzly bears